Purwarupa Sistem Pemesanan Menu Makanan Dan Minuman Menggunakan Qr-Code Berbasis Web - Tri Listyorini; Endang Supriyati; Noor Hisyam, Muhammad Dany (Yayasan Literasi Sains Indonesia, 2022)
The combination of the web and QR-Code technology can create a food and beverage menu ordering system that can help the waiter's duties so that services can be carried out evenly by utilizing Qr-Code technology for ordering menus with the scanner device being an android smartphone. Payments can also be made using your name or table number and can be made at the cashier or customers simply request a bill at the table. That way the waiter doesn't need to take orders one by one and it's easier for customers to make payments